EDUCATIONAL AND TRAINING SKILLS IN MEDICAL EDUCATION - Moraes Armesto , Leonardo (Health and Society, 2023)
Medical practice is a process of constant professional reverberation in order to deepen its joint relationship with the patient. To this end, a given approach must be built from their training process in the early years of the medical course, based on a series of skills that make them educationally more human and close to the nuances, difficulties and layers that involve health care .